Formation of the BeH+ and BeD+ Molecules in Be+ + H/D Collisions Through Radiative Association - Szabó, Péter; Góger, Szabolcs; Gustafsson, Magnus (Frontiers in Astronomy and Space Sciences, 2021)
Cross sections and rate coefficients for the formation of BeH$^{+}$ and BeD$^{+}$ molecules in Be$^{+}$ + H/D collisions through radiative association are calculated using quantum mechanical perturbation theory and Breit-Wigner theory. The local thermodynamic equilibrium limit of the molecule formation is also studied, since the process is also relevant in environments with high-density and/or strong radiation fields. The obtained rate coefficients may facilitate the kinetic modelling of BeH$^{+}$/BeD$^{+}$ production in astrochemical environments as well as the corrosion chemistry of thermonuclear fusion reactors.